2009
DOI: 10.1002/lapl.200910082
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient continuous-wave 912 nm Nd:GdVO4laser emission under direct 880 nm pumping

Abstract: The quasi-three-level 912 nm continuous-wave laser emission under direct diode laser pumping at 880 nm into emitting level 4 F 3/2 of Nd:GdVO 4 have been demonstrated. An endpumped Nd:GdVO 4 crystal yielded 8.1 W of output power for 13.9 W of absorbed pump power. The slope efficiency with respect to the absorbed pump power was 0.679. To the best of our knowledge this is the first demonstration of such a laser system. Comparative results obtained for the pump with diode laser at 808 nm, into the highly-absorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…A well known representa tive is Nd:YVO 4 , which has been widely used both in research and commercial devices. Another vanadate crystal, Nd:GdVO 4 , which was confirmed to be supe rior to Nd:YVO 4 in thermal properties, was also inves tigated extensively [22][23][24][25][26][27][28][29][30][31][32]. A more efficient pumping method was presented recently, which was to pump the Nd 3+ ions directly into the 4 F 3/2 upper lasing level.…”
Section: Introductionmentioning
confidence: 97%
“…A well known representa tive is Nd:YVO 4 , which has been widely used both in research and commercial devices. Another vanadate crystal, Nd:GdVO 4 , which was confirmed to be supe rior to Nd:YVO 4 in thermal properties, was also inves tigated extensively [22][23][24][25][26][27][28][29][30][31][32]. A more efficient pumping method was presented recently, which was to pump the Nd 3+ ions directly into the 4 F 3/2 upper lasing level.…”
Section: Introductionmentioning
confidence: 97%
“…Successful attempts to lase the Nd:LuVO 4 have been reported [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Recently, the Nd:LuVO 4 laser under direct 880 nm diode laser pumping was reported [53][54][55][56][57][58]. In 2010, Lü et al reported diode pumped Nd:LuVO 4 laser emitting at 1089 nm for the first time.…”
Section: Introductionmentioning
confidence: 98%
“…The corresponding fre quency doubled blue lasers [26][27][28][29][30][31][32] were also in mod erate progress. This transition is usually used to design lasers in vanadate crystals or at 946 nm in Nd:YAG crystal [33][34][35][36][37][38][39][40][41][42]. Recently, the laser operation of disor dered Nd:LGS around 1064 and 904 nm has been studied [43,44], which demonstrated that LGS is an excellent laser host for Nd ions.…”
Section: Introductionmentioning
confidence: 99%